Compliance Of Disclosure Of Material Topics In Sustainability Report Gri Standard: Content Study - Handojo, Shahab Rahmadianto; Sukoharsono, Eko Ganis (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
The objective of this research is to analyze and identify the trend of PT Pertamina (Persero) in complying with the GRI Standard. The grounding theory is the stakeholder theory, in which stakeholders’ demand to companies encompasses economic, social, and environmental aspects. In this study, content analysis was utilized to measure and evaluate the said compliance. It was used to identify, analyze, categorize, and compile such compliance by analyzing information reported using the required indicators. This study finds that the compliance of PT Pertamina (Persero) with the GRI Standard from 2022 to 2022 has increased. Its score in 2020 was 76%, categorized as “compliant”; while the score in 2021 was 83%, categorized as “highly compliant”; and the score in 2022 was 90%, categorized as “highly compliant”. Therefore, this study concluded that PT Pertamina (Persero) is committed to the fulfillment of sustainable development and its stakeholders’ demand.